Acolhimento humanizado no cuidado à pessoa idosa em unidade ambulatorial: proposta de fluxograma - Ancelmo, Maria das Neves da Silva (2018)
Introduction: population aging is a global phenomenon that, recently, has been gaining greater importance in developing countries. The increase in this population has caused effects already perceived in the social demands in the areas of health and welfare. Health professionals should understand the welcoming of elderly people as a matter of the aging process, aiming to facilitate the access to the various care levels in health services. Objectives: To identify factors associated with the humanized welcoming for the elderly person in an outpatient unit, from the literature in the area and draw a flowchart of humanized welcoming in care for the elderly person to the Outpatient sector of the Lauro Wanderley University Hospital/ Brazilian Company of Hospital Services. Method: This is a methodological study developed in two stages: the first was an integrative review of the literature on the humanized welcoming in care for the elderly person in outpatient unit and the second was the elaboration of a flowchart of humanized welcoming in care for the elderly person to the Outpatient Sector. The thematic categories identified in the integrative review resulted in the development of the flowchart of the elderly person to the Outpatient sector of the aforementioned institution, emphasizing the humanized welcoming for the elderly person. Results: Some factors are associated with the humanized welcoming for the elderly person, which constitute the thematic categories identified in the study: dialog, listening, trust, bonds, risk classification, orientation, referral, resolubility and improvement of services. The thematic categories served as the basis for the elaboration of the flowchart Humanized Care in care for the elderly person to the Outpatient Sector, emphasizing the humanized welcoming for the elderly person. Final Considerations: the factors associated with the humanized welcoming for the elderly person identified in the study allowed preparing the flowchart Humanized Care in care for the elderly person in the Outpatient Sector, and professionals from the hospital, professors and students during the process of teaching and learning in the clinic should use it, contributing to the qualified nursing assistance and to future nursing researches.